2021
DOI: 10.1186/s13075-021-02458-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrating transcriptome-wide association study and mRNA expression profile identified candidate genes related to hand osteoarthritis

Abstract: Background Osteoarthritis (OA) is a common skeletal system disease that has been partially attributed to genetic factors. The hand is frequently affected, which seriously affects the patient’s quality of life. However, the pathogenetic mechanism of hand osteoarthritis (hand OA) is still elusive. Methods A genome-wide association study (GWAS) summary of hand OA was obtained from the UK Biobank dataset, which contains data from a total of 452,264 Whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…On the other hand, the distinguished clinical appearance between male and female patients warrants the mechanistic investigation at the molecule level. In the current study, the global gene expression profiles of knee joint articular cartilage from male and female donors of a well-accepted dataset [33][34][35][36][37][38][39][40][41][42], GSE114007, were comprehensively compared to gain insight into the understanding of the SABV not only in the healthy status, but also in the response of OA stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the distinguished clinical appearance between male and female patients warrants the mechanistic investigation at the molecule level. In the current study, the global gene expression profiles of knee joint articular cartilage from male and female donors of a well-accepted dataset [33][34][35][36][37][38][39][40][41][42], GSE114007, were comprehensively compared to gain insight into the understanding of the SABV not only in the healthy status, but also in the response of OA stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…As a powerful genebased method, TWAS has been successfully applied to decipher the genetic architecture of several complex traits. [9][10][11][12] The majority of existing TWAS studies calculated genetic-expression matrix in each tissue separately, which might neglect the sharing local regulation of gene expression across different tissues. 13 Evidence has shown that eQTL with large effects can regulate gene expression across multiple tissues.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The effect of genes on immune infiltration was evaluated. The level of immune cell infiltration in each sample was quantified by single sample gene set enrichment analysis (ssGSEA) (24). Spearman correlation analysis was performed on gene expression and immune cell content.…”
Section: Immune Gene Correlation Analysismentioning
confidence: 99%